Identificación de Alternaria brassicae en el cultivo de col (Brassica oleracea) en el Barrio Santa Rosa, Cantón Montúfar - Cangás Hernández, Danny Ricardo (2019)
SUMMARY The research was carried out in its entirety in the Santa Rosa neighborhood, CantónMontúfar and it was directly aimed at identifying the presence of Alternariabrassicae in the cabbage crops (Brassica oleracea) that exist in the area, for this purpose it was proposed in the chapter I an introduction where we synthesized the reality of the cultivation of vegetables at a global, national and local level as well as information on the alternaria was addressed, in this chapter we can also find the specific objectives that we set ourselves: 1) Determine the causes that cause the emergence of alternaria (Alternariabrassicae) in cabbage crops (Brassica oleracea), 2) Propose ways to prevent and combat alternaria (Alternariabrassicae) in cabbage crops (Brassica oleracea), 3) Establish the level of knowledge that the people who are dedicated to the cultivation of cabbage (Brassica oleracea) have to implement controls and methods of eradication of the rnaría (Alternariabrassicae). In chapter II we found relevant and important bibliographical information on the two main actors of the research, the alternaria and the col. Chapter III describes the methodology to be used for the analysis of the information collected, as well as the materials and equipment needed to carry out the research, and the technique for gathering information in the field. In chapter IV, the results obtained are determined through an analysis of all the information collected. Finally, chapter V presents a series of conclusions reached during the development of the research and aided by the accumulated information, as well as some recommendations that are expected to be followed for the growth of this type of crops in favor of the farmers and those who depend on them. Keywords: cabbage, fungus, crop, production, infection, organic, environmental, control, chemicals, plants.